Distorsi Checks and Balances Dalam Penggunaan Hak Angket DPR Terhadap KPK: Kajian Yuridis Normatif atas Kesenjangan Das Sollen dan Das Sein - Karunia Rahmawati; Muhammad Jefri Kurniawan (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This paper critically examines the legislative oversight mechanism through the Indonesian House of Representatives' (DPR) inquiry rights (hak angket) in relation to the principle of checks and balances in Indonesian constitutional law. The study focuses on the 2017 Special Committee (Pansus) inquiry against the Corruption Eradication Commission (KPK), which triggered a sharp constitutional interpretation divide. Using a normative juridical approach through statutory, conceptual, and case study analyses, this paper identifies a substantial gap between the ideal construction (das sollen) and actual practice (das sein) of the principle. The Constitutional Court Decision No. 36/PUU-XV/2017 classifying KPK within the executive branch opened pathways for politicization of an integrity enforcement institution. The inquiry process reflected political pressure rather than constructive policy evaluation, ultimately contributing to the systematic weakening of KPK through the 2019 KPK Law Revision. This study argues for normative restoration to reposition KPK as a genuinely independent state auxiliary organ, free from political power intervention.